Jender Dan Tanggung Jawab Kredit UMKM - Lailah Fujianti (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
Previous research revealed that women are more responsible for loan repayment (D'Espallie at all, 2011;AgierandSzafarz, 2013 and BoeheandCruz, 2013). The aim of this research to verification of the results of previous research whether there is a difference between men's and women's responsibilities in terms of loan repayment onSMEs in Indonesia and to find out who is more responsible man or woman. The samples were SMEs in Depok and Bogor as many as 65 people were taken by purposive sampling. Methods of data analysis is Mann Whitney two independent samples. The results howed significant differences in loan repayment responsibilities between men and women. Women are more responsible for repayment than men.